Patients' Socio-Economic Status, Tobacco and Medical History Associated with Implant Failure - Georgios S. Chatzopoulos; Larry F. Wolff (University of Zagreb. School of Dental Medicine, 2018)
Objective: To examine the potential association between patients' characteristics that experienced implant failure and those who had successful implant treatment. Materials and methods: This retrospective case-control study is based on 186 dental records of implant failure and 186 age and gender matched successful treatments for a total of 372 patients. Age at the time of the procedure, gender, medical history, tobacco use, dental insurance status, ZIP code and type of treatment provided (implant failure/successful implant treatment) were recorded. Results: The population consisted of 47.6% females, 48.9% individuals with dental insurance and 9.7% self-reported tobacco users. A statistically significant association (p≤0.05) was found between implant failure and successful implant treatment in regards to tobacco use, socio-economic status and medical history. Insurance status and implant location (region, arch) did not affect significantly (p>0.05) the outcome of implant therapy. Conclusions: Within the limitation of this retrospective case-control study, individuals with high socio-economic status, no history of tobacco use and history of heart attack were more likely to have a successful implant treatment than those with a low socio-economic status, tobacco users and without history of heart attack.